PENGGUNAAN PAPAN SEMAT SEBAGAI MEDIA PENGENALAN KONSEP MATEMATIKA PADA ANAK USIA 5-6 TAHUN - Azkiya Maemunah; Dede Dhiyaul Auliyah; Hani Febriani; Putri Diana Hayati Nufus; Rr. Deni Widjayatri (incrementapedia, 2022)
This study aims to introduce the concept of mathematics for children aged 5-6 years with fun educational media, namely the pinned board. Pinboard is one of the learning media that is used by pinning. The introduction of mathematics in kindergarten is still fairly low because it only learns concepts and number symbols, addition, and subtraction. Therefore, the readiness of preschool children in understanding mathematical concepts must still be given further stimulation by using various interesting and easy media. This type of research is a descriptive qualitative method with an observation data collection process. The results of this study explain that the introduction of mathematical concepts with the semat board media in children aged 5-6 years at the State Kindergarten Pembina Serang City is quite good, because the children in the kindergarten can already mention the number symbols, triangular, circular and square shapes and can also count the number of shapes contained on the pinned board. The subjects in this observation were 5 children, where there were 2 children who had difficulty in doing this, therefore the researcher tried to make creative media and not that in order to support the math learning process.